Public Policies of Bilingualism towards Social Peace - Díaz, Alba Milena Ríos; Díaz, Carmen Helena Romero; Novikova, Olga; Zamora, Maigualida; Giraldo, Nelson Eduardo Castaño; Molina, César Ernesto Zapata- (International Journal of Membrane Science and Technology, 2023)
The objective of this study is to analyze bilingualism in Colombian educational public policies and academic management committed to healthy coexistence and social peace in elementary and middle school education. It is mixed research, and the data processing techniques are textual analysis of written documents and descriptive statistics of data from surveys applied to teachers. The main findings explain that public bilingualism policies do not achieve satisfactory results due to the lack of procedures that involve the different actors of the educational system. The bilingual curriculum represents the means of implementation of these policies in the educational institution and urgently requires an update that includes its actors recognizing their needs, where shared learning represents a vital foundation for socialization from the classroom, guaranteeing the development of communicative skills among different groups of students and promoting harmonious coexistence that sustains social peace. Public policies for bilingualism require updating with strategies and trained human capital for the development of a curriculum that facilitates its effectiveness, considering learning as a promoter of social peace.